Serum Levels of Proinflammatory Biomarkers in Military Recruits with and without Metabolic Syndrome - Abdulrahman K. Al Asmari; Hamoud A. Al Shehri; Haseeb A. Khan; Saud Al Omani; Saeed G. Kadasah; Ghaleb B. Horaib; Ahmed Al Buraidi; Abdullah A. Al Sharif; Fayez S. Mohammed; Rajamohamed Abbasmanthiri; Nasreddien M. Osman (Mediators of Inflammation)
Objectives. Inflammatory mediators are associated with many chronic diseases; however, their role in metabolic syndrome (Met-S) is not well documented. We therefore aimed to compare the serum markers of inflammation including C-reactive protein (CRP), myeloperoxidase (MPO), interleukin-6 (IL-6), tumour necrosis factor alpha (TNF-α), and TNF-β in young military recruits with and without Met-S. We hypothesized that any significant change in inflammatory markers between the two groups would indicate the role of inflammation in Met-S that would help in future directions for screening and treatment of Met-S. Design and Methods. A total of 2010 adult men, aged 18-30 years, were divided into two groups: with Met-S (N=488) and without Met-S (N=1522), according to the International Diabetes Federation definition. We compared the serum levels of inflammatory biomarkers between the two groups. We also studied the correlations between the inflammatory markers and the components of Met-S to explore the biomarker potential of inflammatory markers for screening of Met-S. Logistic regression analysis was performed to test the association between inflammatory markers and Met-S. Results. A large number of subjects in the Met-S group were suffering from obesity. Out of the 2010 total subjects, only 731 (36.4%) had normal fasting blood sugar (FBS), while the prevalence of prediabetes and diabetes was significantly higher in subjects with Met-S. We observed significant increases in serum levels of CRP, MPO, IL-6, and TNF-β but not TNF-α in subjects with Met-S as compared to subjects without Met-S. All the markers of inflammation showed significant correlations with Met-S, triglycerides (TG), blood pressure, body mass index (BMI), and age; however, none of these markers were correlated with HDL. Logistic regression analysis showed a significant association between Met-S and inflammatory markers. Conclusions. Serum levels of CRP, MPO, IL-6, and TNF-β are significantly increased in young adults with Met-S. This is probably the first study reporting TNF-β levels in Met-S. Since a proinflammatory cascade precedes many years before the onset of cardiovascular disease, these inflammatory biomarkers could help in the monitoring of high-risk individuals with Met-S who will be requiring therapeutic intervention.